2013
DOI: 10.1002/oby.20191
|View full text |Cite
|
Sign up to set email alerts
|

Effects of diet macronutrient composition on body composition and fat distribution during weight maintenance and weight loss

Abstract: Qualitative aspects of diet may affect body composition and propensity for weight gain or loss. We tested the hypothesis that consumption of a relatively low glycemic load (GL) diet would reduce total and visceral adipose tissue under both eucaloric and hypocaloric conditions. Participants were 69 healthy overweight men and women. Body composition was assessed by DXA and fat distribution by CT scan at baseline, after 8 weeks of a eucaloric diet intervention, and after 8 weeks of a hypocaloric (1000 kcal/d defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 19 publications
5
50
0
1
Order By: Relevance
“…As previously reported (27), in the eucaloric phase, loss of IAAT was significantly greater (P < 0.05; Figure 1A) in participants who consumed the lower-carbohydrate diet (11%) than in those who consumed the lower-fat diet. Furthermore, when comparing the 2 diet groups at the end of the eucaloric phase, participants who consumed the lower-carbohydrate diet had 11% less intraabdominal fat (IAAT) than did those who consumed the lowerfat diet (P < 0.05, adjusted for total fat mass and baseline IAAT).…”
Section: Resultssupporting
confidence: 72%
See 1 more Smart Citation
“…As previously reported (27), in the eucaloric phase, loss of IAAT was significantly greater (P < 0.05; Figure 1A) in participants who consumed the lower-carbohydrate diet (11%) than in those who consumed the lower-fat diet. Furthermore, when comparing the 2 diet groups at the end of the eucaloric phase, participants who consumed the lower-carbohydrate diet had 11% less intraabdominal fat (IAAT) than did those who consumed the lowerfat diet (P < 0.05, adjusted for total fat mass and baseline IAAT).…”
Section: Resultssupporting
confidence: 72%
“…Sixty-nine men and women aged 21-50 y were enrolled in the study. Details of the study were published previously (25)(26)(27). Briefly, inclusion criteria were BMI (in kg/m 2 ) of 25-45, weight <136 kg, age 21-50 y, nondiabetic, and no weight change of >2.3 kg over the past 6 mo.…”
Section: Methodsmentioning
confidence: 99%
“…1,29,30 Several studies have reported that evening-type individuals have a less healthy lifestyle than morning-types, with unfavorable dietary habits. 2,28 Nevertheless, in the current population, we did not find significant differences in dietary intake characteristics (total energy intake and macronutrient distribution) between evening and morning chronotypes.…”
Section: Discussionmentioning
confidence: 99%
“…However, our results demonstrate that the retention in BCM and LBM in HP group was probably not caused by an increase in physical activity, because these levels were similar in both groups [31]. Studies suggest that high GL diets and elevated insulin response might preserve the release of free fatty acids from adipose tissue due to the lipogenic actions of insulin, which maintain the BFM [40]. Considering the HC formula diets was classified as high GL food and the HP as low GL food [41] we found similar reduction of BFM after consumption of both formula diets.…”
Section: Discussionmentioning
confidence: 78%